Mind Mapping Technique with Think Pair Share Strategy Towards Writing Ability in Descriptive Text - Erfiyanti, Eko; ., Mustaji; Danu R, Retno (Journal of Education Research and Evaluation, 2019)
This research is applied to tenth graders of SMKN 1 Pungging to investigate the influence of teaching writing descriptive text ability using mind mapping technique with think pair share strategy. This population of this research is the tent graders that consist of 620 students which is taken 64 students as the sample. There are two classes; they are X TKJ 1 which is applied by teaching writing descriptive text using mapping technique with think pair share strategy and X TKJ 2 which is taught writing descriptive text by conventional technique. However, both of the groups were taught the same materials based on the curriculum. This study used pretest-posttest non-equivalent control group design for experimental and control groups. The pre test and post test were administered not only to the experimental group but also the control group. The pre test is as starting point to verify the condition of both groups. Finally,Â  at the end of the treatment, the experimental group and the control group received a post test; the result of the post test was to define the significance difference between the experimental group and the control group. The result is there is significance difference between the classes which is taught writing descriptive text using mind mapping technique with think pair share strategy and which is taught writing descriptive by the conventional technique. The result calculated by SPSS 20.0; it is a computer program statistical calculation and the result is further discussed in Hypothesis Testing. It is approved that the mean of post-test of experimental group is increased from 58.28 to 80.16. It can be noticed that the mean of the post-test of experimental is 21.72 higher than the mean of post-test of control group.Â Â